Implications of Physical Activity in Reducing Alcohol Use for Women Veterans: A Narrative Review - Alfredo Gil; Donna Schuman; Keng-Yu Chang; Zhaoli Liu; Chueh-Lung Hwang (Women's Health Reports)
Women veterans (WV) are a fast-growing population in the United States with concerning health disparities. Reports of increased risks of cardiovascular disease (CVD) and poorer health are evident in WV compared with their civilian counterparts. The transition from active duty to veteran poses additional life stressors, causing changes in health behaviors such as unhealthy alcohol consumption and decreased physical activity, which may explain health disparities in WV. The changes in these two health risk behaviors may be influenced by each other, and emerging evidence suggests that physical activity aids in managing alcohol consumption during alcohol use treatment. In this general narrative review, we summarized findings from studies involving WV on (1) the associations between alcohol consumption and physical activity and (2) the effect of physical activity on reducing alcohol use. We also discussed the clinical consideration of adding physical activity to alcohol use interventions for WV. Most of the literature included in this review has been based on predominantly veteran men populations. This knowledge gap highlights the importance of continued efforts and research studies targeting WV to eliminate health disparities among them.